The mitochondrial permeability transition pore as a mediator of ischaemic preconditioning. (22nd September 2015) - Davidson, SM; Lim, SY; Yellon, DM; Hausenloy, DJ
Abstract : Introduction: We have previously demonstrated that the mitochondrial permeability transition pore (mPTP) is required for ischaemic preconditioning (IPC), but the reason for this is unclear. IPC protects the heart by generating mitochondrial reactive oxygen species (ROS) and phosphorylating Akt and Erk1/2. We hypothesised that the mPTP is required for IPC to generate mitochondrial ROS and phosphorylate Akt and Erk1/2. Methods: Mice lacking cyclophilin-D (CYP-D −/− ), a critical component of the mPTP, and B6Sv129F1 control mice were treated as follows: (1) reversible mPTP opening was detected as a reduction in mitochondrial calcein fluorescence in cardiomyocytes over the course of 30 minutes normoxic incubation; (2) isolated cardiomyocytes were subjected to hypoxic preconditioning (HPC; 10 minutes hypoxia/reoxygenation) and cell survival was determined using propidium iodide staining following 60 minutes hypoxia in an air-tight chamber followed by 30 minutes reoxygenation; (3) isolated cardiomyocytes loaded with reduced mitotracker red (to measure ROS) were subjected to hypoxic preconditioning (15 minutes hypoxia/reoxygenation) and mitotracker red fluorescence was measured; (4) mice were subjected to a standard in-situ myocardial preconditioning protocol (5 minutes ischaemia/reperfusion) and the hearts were examined for levels of Akt and Erk1/2 phosphorylation using Western blotting. Results: Under basal conditions reversible mPTP opening (as measured by the reduction in mitochondrial calcein fluorescence) was found to be greater in wild-type cells when compared with CYP-D −/− p<0.01). Hypoxic preconditioning enhanced reversible mPTP opening to a greater extent in control compared with CYP-D −/− cardiomyocytes (53 ± 2% in control vs 17 ± 3% in CYP-D −/− ; N >27 cells/group; p<0.01). In addition, HPC increased mitochondrial ROS production (as measured by increased levels of reduced mitotracker red fluorescence) in the wild-type cells when compared with the CYP-D −/− cells (by threefold; N >100 cells/group; p<0.05) and improved cell survival following simulated ischaemia–reperfusion injury in the wild-type cells but not in those lacking CYP-D (53 ± 2% in control vs 17 ± 3% in CYP-D −/− ; N >27 cells/group; p<0.01). In situ myocardial preconditioning of intact murine hearts (5 minutes ischaemia/reperfusion) resulted in the phosphorylation of Akt and Erk1/2 phosphorylation in control hearts but not in CYP-D −/− hearts. Conclusion: The mPTP is critical to IPC protection as it is required for the generation of mitochondrial ROS and the phosphorylation of Akt and Erk1/2, critical steps in the IPC signalling pathway.